2018
DOI: 10.1002/apj.2272
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of activated carbon from spent catalyst with mercury by microwave‐induced CO2 activation

Abstract: This study reported the regeneration of mercury‐loaded porous carbon catalyst utilized in the manufacture of PVC (Polyvinyl chloride) resin using the combined effect of microwave heating and CO2 purging. The porosity, functional, and surface chemistry was featured by means of low‐temperature nitrogen adsorption, scanning electron microscopy, Fourier‐transform infrared spectroscopy, Raman spectroscopy, and X‐ray photoelectron spectroscopy. The result showed that the iodine number, methylene blue adsorption, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The bands at 866 cm −1 is attributed to C−H out‐of‐plane deformation vibrations of the ring. A weak characteristic peak at 692 cm −1 can be seen clearly, certifying the existence of C−Cl [34] . During the first cycling process, C−Cl bond cannot be seen when Li + ion insertion into PPy structure, while C−Cl bond appears when Li + ion extraction from PPy structure.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The bands at 866 cm −1 is attributed to C−H out‐of‐plane deformation vibrations of the ring. A weak characteristic peak at 692 cm −1 can be seen clearly, certifying the existence of C−Cl [34] . During the first cycling process, C−Cl bond cannot be seen when Li + ion insertion into PPy structure, while C−Cl bond appears when Li + ion extraction from PPy structure.…”
Section: Resultsmentioning
confidence: 91%
“…A weak characteristic peak at 692 cm À 1 can be seen clearly, certifying the existence of CÀ Cl. [34] During the first cycling process, CÀ Cl bond cannot be seen when Li + ion insertion into PPy structure, while CÀ Cl bond appears when Li + ion extraction from PPy structure. After 50 cycles, the weak CÀ Cl bond cannot be seen which may be attributed to the microstructure change of PPy.…”
Section: Chemsuschemmentioning
confidence: 99%
“…[ 64 ] Therefore, employing alternative energy sources such as microwave irradiation can reduce the energy usage and other negative environmental impacts of synthesis processes, which is of high importance. In literature, there are many papers devoted to pyrolysis, [ 65–74 ] activation, [ 75–98 ] and even regeneration of spent carbons [ 99–106 ] under microwave radiation. Recently, excellent reviews were reported to summarize the main accomplishments in the microwave‐assisted synthesis of biomass‐derived porous carbons.…”
Section: Microwave Synthesis Of Nanoporous Materials and Their Applicationsmentioning
confidence: 99%
“…Porous carbons obtained via microwave‐assisted methods with their SSA values and potential applications are summarized in Table 4 . [ 65–122 ]…”
Section: Microwave Synthesis Of Nanoporous Materials and Their Applicationsmentioning
confidence: 99%